CONSUMER PROTECTION AND INvESTMENT STRATEGY ON THE INSURANCE MARKET: ITALIAN AND RUSSIAN ExPERIENCE - N. V. Kirillova; A. Bellucci (Финансы: теория и практика)
The main areas in protection of consumers of insurance services are as follows: correct actuarial valuation of insurance liabilities, formation of insurance reserves, devising an investment policy, raising the solvency of insurance organizations, proper information about insurance relations. The paper examines the above-mentioned issues. The present work is the outcome of studies performed with extensive use of basic and applied research works conducted by Russian and foreign specialists. This work is based on statistical data from Italian and Russian insurance markets, regulatory documents, insurance supervision as well as data from Federal State Statistics Service and data from foreign sources. The methods of systemic analysis proved to be an effective tool in investigation. The article explores Italian and Russian experience in the field of protection of consumers of insurance services highlighting those aspects of the Italian experience that can be put into practice on the Russian insurance market. This study may be of interest for participants of the insurance market, especially for the corporate sector and analysts involved in establishing insurance relations aimed to protect the rights and interests of consumers of insurance services.